Pouvoirs en conflit dans le personnage de Jane Shore dans The First and Second Parts of King Edward IV de Thomas Heywood - Frédérique Fouassier (Anglophonia)
In The First and Second Parts of King Edward IV, Thomas Heywood gives a patriarchal and Calvinist interpretation of the very popular story of King Edward IV and his mistress Jane Shore. This paper purposes to study the skein woven by the concepts of femaleness, conflict and power in Heywood’s Jane Shore, by comparing her to other Renaissance versions of her character. She unwillingly arouses Edward’s desire, unaware as she is of the power of her beauty on men. She decides to use her status as a courtesan to help those in need. But there is no possibility for a Calvinist Mary-Magdalene, and Jane dies in utter destitution, stressing her didactic value to women in the audience.